Small organisms create big problems for taxonomists - Leduc, Daniel (New Zealand Science Review, 2016)
​ The age of travelling naturalists such as Wallace, Darwin, and von Humboldt who explored newly discovered continents and islands and described their animal and plant biodiversity is now well and truly over. Understandably, the work of early explorers usually focused on the large and conspicuous organisms that they saw; as a result, we now have a good knowledge of the diversity of these large organisms, although a relatively small number of mammals, birds, and fish species continues to be described every year across the globe. In an attempt to find more new and exotic species, biologists have more recently turned their attention to environments which until not long ago were inaccessible or difficult to sample, such as the polar regions and the deep sea. In these environments, undescribed species and higher taxa are abundant and the diversity is sometimes very high. However, less remote environments are also home to undiscovered biodiversity. Instead of standing on the bow of a ship scrutinising the horizon (à la Jacques Cousteau), we now need to crouch down, sift through unsightly piles of often smelly dirt and debris, and spend hours bent over a microscope. We need to pay more attention to the very small organisms right under our nose, and we need to think small.